Effect of Social Media Marketing on Consumer Based Brand Equity and Word of Mouth: A Case Study of Eastern Mediterranean University - Sagynbekova, Sabira (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
This study sought to analyze the effects of social media communication in terms of user-generated and firm created social media communication on brand equity and word of mouth. The research took place within the scope of Eastern Mediterranean University, Famagusta, TRNC. A quantitative research method was adopted for the purpose of this research. A substantial number of survey questionnaires were administered and a considerable number of responses were generated which served as data for this research. Also appropriate analysis was carried out to ensure the responses gotten were valid enough for further analysis and drawing conclusions. The results of the analysis conducted depicted that social media communication (firm-created and user-generated) had significant effects on overall brand equity and word of mouth respectively. However their level of effects on each of the dependent variables differed from each other suggesting other factors also contributed to the effects. It further confirms the research in previous works on the importance of social media communication and its role in building brand equity and generating positive word of mouth. This study suggested that universities (including organizations) take advantage of the social media by engaging their respective clients online in terms of attending to complaints, providing adequate and necessary information especially through facebook which would in turn build a level of involvement and rapport with students and clients.

ÖZ: Bu çalışmanın amacı sosyal medya iletişim etkilerini kullanıcı ve firma odaklı medya iletişiminin marka değerine ve ağızdan iletişime etkisini incelemektir. Araştırma Doğu Akdeniz Üniversitesi, Gazimağusa’da gerçekleştirilmiştir. Çalışmada kantitatif araştırma yöntemi kullanılmıştır. 177 kişiden analize değer veri toplanabilmiş ve araştırma kapsam ve amacına yönelik gerekli istatistiksel yöntemler kullanılmıştır. Araştırma sonuçları sosyal medya iletişiminin (firma taraflı ve kullanıcı tarafından oluşturulan) genelde marka değerine ve ağızdan iletişime anlamlı ve önemli bir etkisi olduğunu göstermiştir. Sosyal medyanın bileşenlerinin genel marka değeri ve ağızdan iletişime etkisi farklı olduğu gözlenmiş ve çalışmamızda tartşılmıştır. Çalışmamız daha önce yapılan araştırmalardaki bulguları da doğrulamıştır. Çalışma üniversitelerin sosyal medya avantajlarını kullanmasını ve şikayetleri bu yöntemle çözmesini önermektedir.
Master of Arts in Marketing Management. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2016. Supervisor: Prof. Dr. Mustafa Tümer.
Keywords: Business Administration; Marketing Management; Social Media--Customer relations--Brand Equity; Social media--Branding (Marketing); Social Media Communication; Firm-created Social Media Communication; User-Generated Social Media Communication; Word of Mouth